A computer aided system to automate the restoration of electrical power supply - Teo, C.Y. (Electric power systems research, 1992)
An innovative computer-aided system for the restoration of supply in a power distribution network using a fast restoration algorithm complemented by a step-by-step partial restoration algorithm is described. This restoration system is designed to be linked to a supervisory control and data acquisition (SCADA) system. A rule based system is used to generate a hypothesis in fault diagnosis to identify the type of fault and its location. The fast restoration algorithm with built-in multiple search for all possible links to connect the dead islands in the network is augmented by a load flow simulation. It thus enables a very fast and total restoration of supply with a minimum of switching actions. The additional step-by-step partial restoration algorithm will further restore supply, utilizing up to the maximum capacity of the distribution system. The proposed restoration system can be implemented on an existing SCADA system to provide a restoration guide for an operator or for automatic restoration.